Can Money Buy Advocacy? The Moderating Role of Referral Programs in B2B SAAS - Muh Arif Mahfudin; Ngatno Ngatno (Journal of Economics and Business UBS, 2026)
The cost of acquiring new customers in SaaS companies requires companies to have an effective strategy. A strategy that is often applied is a referral program, although its effectiveness is unclear. This study discusses customer advocacy influenced by Trust, Security, Customer Satisfaction and Ease of Use in the financial SaaS environment. This study extends the UTAUT framework by integrating the moderating role of the Referral Program on the relationship between driving variables and advocacy. Respondents were 202 from "CARDS" users, namely SaaS companies in Indonesia in the field of Fintech Education. The results of the analysis using SEM-PLS showed that Customer Satisfaction was the main driving factor for Customer Advocacy (β = 0.438, p < 0.001), followed by Trust (β = 0.254, p < 0.01). Meanwhile, Security and Ease of Use did not significantly influence advocacy. The most important finding is that the Referral Program does not directly encourage advocacy actions (β = 0.038) but significantly moderates the relationship if customer satisfaction and trust have been established. In this study, it can be concluded that in B2B SaaS, especially in fintech in the educational institution sector, monetary incentives are not the main thing in driving advocacy, but rather post-adoption behavior is driven by performance results.